The Ego as a Survival Strategy of Scheherazade in Shahrazad by Tawfiq al-Hakim: A Sigmund Freud Psychoanalytic Analysis - Samara, Arbila Dwi (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the psychological dimension of the ego in the character of Syahrazad in the drama written by Taufiq al-Hakim through a literary psychology approach based on the psychoanalytic theory of Sigmund Freud. The purpose of this study is to analyze the representation of the ego aspect in Syahrazad’s personality and to explain the role of the ego in her survival strategies when facing conflicts and psychological pressure. The main problem discussed in this research is how the representation of the ego aspect is portrayed in Syahrazad’s personality in the drama. This research employs a qualitative descriptive method with content analysis techniques. The study is categorized as library research, with the drama text Syahrazad by Taufiq al-Hakim serving as the primary data source. Data collection techniques were carried out through systematic reading and note-taking. The findings reveal that Syahrazad demonstrates a dominant ego aspect reflected in her ability to control emotions, understand the psychological conditions of others, and formulate rational strategies in dealing with threats. The role of the ego is also evident in her ability to employ symbolic communication and psychological approaches to protect herself while influencing the transformation of King Syahrayar’s attitude. Therefore, Syahrazad is represented as an intelligent, resilient, and adaptive female figure whose strong ego becomes the primary foundation of her survival ability.